The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.11152/mu-1313
|View full text |Cite
|
Sign up to set email alerts
|

Greyscale and contrast enhanced ultrasonography for characterization of gastric malignant tumors

Abstract: Aims: To evaluate the utility of grey scale ultrasonography (US) and contrast enhanced ultrasonography (CEUS) for characterization of malignant gastric tumors.Material and methods: The study was conducted prospectively and it included a number of 30 patients with malignant gastric tumors diagnosed through upper tract endoscopy and biopsy: 25 adenocarcinomas, 3 lymphomas, and 2 stromal tumors. All the patients were examined by US, followed immediately by CEUS, using both oral and intravenous contrast agents. CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…However, the study performed by Xue et al (2016) did not include any cases of gastric lymphoma, only adenocarcinomas, and this could explain the different vascular kinetics observed [ 34 ]. Furthermore, the study published by Neciu et al (2019), performed on 30 patients, included three cases of gastric lymphoma in which, however, only a qualitative analysis of the CEUS examinations was performed [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the study performed by Xue et al (2016) did not include any cases of gastric lymphoma, only adenocarcinomas, and this could explain the different vascular kinetics observed [ 34 ]. Furthermore, the study published by Neciu et al (2019), performed on 30 patients, included three cases of gastric lymphoma in which, however, only a qualitative analysis of the CEUS examinations was performed [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lymphomas of this group were more likely to have a homogeneous enhancement (7/10) and the presence of comb teeth-like vessels (7/10). In human medicine, enhancement patterns described for gastric lymphomas reported that these tumours are characterized by a variable uptake pattern, intense and heterogeneous enhancement, and a delayed washout [ 35 ]. However, in the mentioned study, the presence of comb teeth-like vessels was not considered, which was instead described by Xue et al as typical of gastritis and not of gastric cancers [ 34 ]: this finding seems to further support, as already highlighted for the increased quantitative contrast uptake values (PE and WiR), that the vascular component of the neoplastic gastric wall, during feline HGAL, maintains increased and aberrant perfusion patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations